Paediatric oral caustic soda ingestion: Case series and lessons learned. Issue 1 (January 2022) - Tavakoli, Milad; Cole-Healy, Zachary; Blackburn, Timothy; Kalantzis, Athanasios; Beale, Victoria
Abstract : Introduction : The ingestion of sodium hydroxide otherwise known as caustic soda causes devasting injuries. Oral complications include microstomia, fibrosis and trismus. We present a case series of paediatric oral caustic soda ingestion injuries and their management by the Oral Maxillofacial (OMFS) team at Royal Manchester Children's Hospital and the lessons learnt from these cases. Methods : A total of 3 cases are presented. The patients had injuries when they were 20, 22, and 30 months old. Treatment modalities ranged from custom splinting, steroid infiltration, scar-release procedures, commissuroplasty, split thickness skin grafts and free tissue transfer. 2 patients were referred years post injury. 1 patient was referred acutely. Results : In one case a radial forearm free flap was used for reconstruction of the commissure and buccal mucosa after several failed contracture release procedures. This improved mouth opening removing reliance of PEG tube feeding. One case had severe injuries remains tracheostomy and PEG tube dependent with pending future reconstructive surgery at an older age. The final case was referred to our department early and custom splints have been used since the injury to maintain mouth opening with some success. Conclusions : Treatment of the complications of oral caustic soda ingestion in the paediatric population is challenging. The cases presented highlight that; relapse following contracture release is common and that in selected cases free tissue transfer can lead to satisfactory outcomes. We advocate early referral to an OMFS team in all cases of severe injury.